Por que as reformas permanecem? A trajetória gradualista de mudanças no setor de infraestrutura rodoviária no Brasil entre 1985-2010 - Correia, Marcelo Bruto da Costa (2011)
This thesis offers an explanation for the existence of government policies that do not achieve stability after critical junctures that affect your equilibrium, focusing on the management of road infrastructure in Brazil. The policy of the sector has been in financial and institutional crisis since the mid-70s, which deepened in the 80's, pressuring the democratic Governments to pursue a reform agenda that involved the review of funding mechanisms and public investment, structural change of the sector´s bodies and competences and partnership with the market through policies of road concessions. Through case studies of the Governments of the New Republic between the years 1985 and 2010, the research answers why the reforms instituted in the sector made a string of failures and partial success, providing new imbalances and further attempts at reform. Through the theoretical framework of institutionalism, we demonstrate that the institutional changes that occurred in Brazil from the end of the 70 contributed to the shaping of a sector more pluralistic and under less autonomy of sectoral bodies, leading to institutional contradictions with which the successive governments coped under strategic dilemmas between keeping political support and pursue a good performance. This interaction between a competitive sector and political strategies resulted in a disjointed balance, which sacrifices performance and demand permanent reform.